Syndrome in question: Gorlin-Goltz syndrome - Pauline Lyrio Ribeiro; João Basílio de Souza Filho; Karina Demoner de Abreu; Marisa Simon Brezinscki; Christine Chambo Pignaton (Sociedade Brasileira de Dermatologia, 2016)
Abstract: The Nevoid Basal Cell Carcinoma Syndrome (NBCCS) is an uncommon disorder caused by a mutation in Patched, tumor suppressor gene. It is mainly characterized by numerous early onset basal cell carcinomas, odontogenic cysts of jaw and skeletal abnormalities. Due to the wide clinical spectrum, treatment and management of its modalities are not standardized and should be individualized and monitored by a multidisciplinary team. We report a typical case in a 30-year-old man with multiple basal cell carcinomas, keratotic pits of palmar creases and bifid ribs, with a history of several corrective surgeries for keratocystic odontogenic tumors, among other lesions characteristic of the syndrome.